Enzymatically crosslinked alginate hydrogels with improved adhesion properties12. Issue 12 (28th March 2015) - Hou, Junxia; Li, Chong; Guan, Ying; Zhang, Yongjun; Zhu, X. X.
<x xml:space="preserve">Abstract</x> Alginate–dopamine (Alg–DA) conjugate, a polymer with catechol side groups instead of phenol groups, gels in situ in the presence of HRP and H2O2. The resulting hydrogels exhibit significantly improved adhesion properties.